A novel device for intraoperative photodynamic therapy dedicated to glioblastoma treatment. (November 2017) - Dupont, Clément; Mordon, Serge; Deleporte, Pascal; Reyns, Nicolas; Vermandel, Maximilien
Aim: Photodynamic therapy (PDT) appears to be a valuable new treatment modality for cancer therapy. Studies have reported successful application of PDT for glioblastoma. Here, we introduce a new device dedicated to intraoperative PDT delivered early after fluoro-guided resection combined with a transfer function that determines the treatment time based on the size of the surgical resection cavity.Materials & methods: First, we describe the device, which is composed of a trocar, a balloon filled with a diffusing solution, and a fiber guide in which a cylindrical light diffuser is inserted. Ex vivo experiments were performed to measure the fluence rate inside biological tissues. A calibration factor was defined to convert power measurements into fluence rate values. Calf brains were used to simulate light propagation in human brain tissue, and the photosensitizer administration effect on optical properties was discussed. The temperature elevation during illumination was evaluated.Results: Light power was measured in tissues surrounding the device during ex vivo experiments. Using the previously characterized calibration factor, power measurements were converted to fluence rate values to obtain the transfer function. No thermal elevation was observed during a 2-h temperature test, and the impact of protoporphyrin IX on brain optical properties was considered negligible.Conclusion: A discussion of experimental precision is presented. The light duration determined by the abacus had a standard deviation of <1 min. This value is weak compared with the total illumination time necessary to treat one patient. The main advantage of our device lies in its straightforward implementation of intraoperative PDT for neurosurgery with acceptable dosimetry and easy treatment time.